2023
DOI: 10.22266/ijies2023.0228.22
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Microscopy Images by Using a Hybrid Technique Based on Adaptive Histogram Equalisation and Fuzzy Logic

Abstract: The enhancement of colour medical microscopy images plays an important role in biological fields. Colour medical microscopy images have the lack of contrast and lighting. In this paper, a robust algorithm for enhancing microscopy images was proposed. In the proposed method, the image was first improved by using Contrast-Limited Adaptive Histogram Equalisation (CLAHE). Then, the luminance channel in the colour space was enhanced on the basis of sigmoid transformation and fuzzy logic. Data containing 50 medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although the restored image remained pale, the procedure produced better results. Hind A. Majeed et al [8] suggested a dialogue algorithm to enhance a medical image taken by a light microscope that has poor contrast by enhancing illumination in the color space using a first and second histogram equation based on the sigmoid, and the study then demonstrated transformation and fuzzy logic.…”
Section: Introductionmentioning
confidence: 99%
“…Although the restored image remained pale, the procedure produced better results. Hind A. Majeed et al [8] suggested a dialogue algorithm to enhance a medical image taken by a light microscope that has poor contrast by enhancing illumination in the color space using a first and second histogram equation based on the sigmoid, and the study then demonstrated transformation and fuzzy logic.…”
Section: Introductionmentioning
confidence: 99%